Relationship Between Smartphone Addictions with Sleep Quality in Adolescents - Asiyah, Siti Nur; Putri, Annisa Yusonia (International Conference on Sustainable Health Promotion, 2018)
The purpose of this study was to determine the relationship between Smartphone addiction and sleep quality in adolescents. This research is quantitative research with a correlation approach using data collection techniques in the form of a Smartphone addiction scale and sleeps quality scale. Research subjects amounted to 75 of the total population of 300 students at High School of Al Falah Ketintang in Surabaya. The sampling technique of this study uses a random sampling technique. For technical data analysis used the non-parametric analysis technique, namely spearman rho analysis. The results showed that the correlation value p = 0.001 <0.05 means that Ha is accepted. The correlation coefficient between two variables is -0.372. This result means that there is a relationship between Smartphone addiction and sleep quality in adolescents. Based on these results it can also be understood that the correlation is negative, thus indicating a reversed relationship, meaning that the higher the Smartphone addiction, the lower the quality of sleep in adolescents.